Growth Rates of Output, Labor Force, Hours, and Productivity - Brems, Hans (The Review of Economics and Statistics, 1957)
i. The problem. Current theoretical growth models of Harrod-Domar type have determined the growth rate, by which is usually meant proportionate rate of growth of net or gross national product. But rates of growth of labor force, hours, and productivity are ignored in such models. This neglect is very much in Keynesian tradition. The static Keynesian model makes no distinction between goods and factors and between level of output (of goods) and level of employment (of factors). Dynamizing Keynesian model, growth models of Harrod-Domar type consequently make no distinction between time path of output and time path of employment. The purpose of present paper is to examine more closely relationship between four growth rates of output, labor force, hours, and output per man hour and in particular ' to find determinants of proportionate rate of growth of output per man hour. For this purpose, a slight disaggregation of Harrod-Domar model becomes necessary. If only two sectors are desired, most obvious division in economy is that between firms and households. We shall therefore consider a closed economy and shall ignore government. For disaggregation purposes, best notation is probably Leontief notation.2 Here, each transaction (x) has two subscripts. The first subscript refers to sector of origin, last refers to sector of destination. The subscript f refers to firms, subscript h to households. Three transactions, shown in Table I, are considered. First, firms plan to purchase